Perception of Counselors Regarding the Contribution to Patients Care by Student Nurses - Leeja Bonny Thomas1, Diana Prasad2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nursing, a profession that recalls the name of the Florence Nightingale is indeed one of the noblest professionsin the world that requires lots of love, care and compassion. However availability of nursing professionalsin this area is below accepted norms per population. [1]This study enables the nurses to know how nurses themselves perceive their own profession and see howothers perceive their profession. It is also important to encourage positive attitude of nurses or non-nursingprofessionals towards nursing profession. [2]On the opposite side it is important to extend patient satisfaction on medical care. The study result helps togeneral policy makers, authorities in health care system and especially nurses to figure on bringing up nursingas a valued profession so that image of nursing are going to be positively changed in several professional,communities and families. [3]